Impact of cellular interference on uplink UAV communications - Tan, Ernest Zheng Hui (2020)
The impact of cellular interference on uplink unmanned aerial vehicle (UAV) communications is analyzed in this paper for a multi-UAV network. Specifically, the outage probability and finite signal-to-noise ratio (SNR) diversity gain of the multi-UAV network is characterized in the presence of interference from uplink UAVs and cellular base stations. We demonstrate that the operational altitude of the multi-UAV network determines the severity of cellular interference across low-to-high transmit power regimes. In particular, UAVs operating at higher altitudes are less affected by cellular interference, with higher finite SNR diversity gains and lower outage probability floors observed. Thus, interference mitigation techniques may have to be considered when multi-UAV networks are operating at low altitudes in areas with cellular networks.